TEACHING COMPOSITION IN FINE ARTS CLASSES - M. T. Noomonova (Academia Science Repository, 2023)
This article consists of observing the Badi culture, life, and figurative tasting through the compassionate in the streamers, imitating Badi thought, ability, and instilling little creative activity.